Synthetic analogue of the natural product piperlongumine as a potent inhibitor of breast cancer cell line migration - Valli, Marilia [UNESP]; Altei, Wanessa; Dos Santos, Ricardo N.; De Lucca, Emilio C.; Dessoy, Marco A.; Pioli, Renan M. [UNESP]; Cotinguiba, Fernando; Cachet, Xavier; Michel, Sylvie; Furlan, Maysa [UNESP]; Dias, Luiz C.; Andricopulo, Adriano D.; et al. (Sociedade Brasileira de Quimica (SBQ), 2017)
Piperlongumine is a natural amide alkaloid isolated from several species of Piper and is described in the literature as selectively cytotoxic to several cancer cell lines. Inhibiting cell migration has gained considerable interest as an approach for discovering antimetastatic agents because this process is fundamental to metastasis. Piperlongumine, selected from cell-based assay screening of NuBBE Database, inhibited the migration of MDA-MB-231 breast cancer cells with an EC50 of 3.0 ï¿½ 1.0 μM by the Boyden chamber assay. A series of five analogous compounds based on the structure of piperlongumine were designed, synthesized and evaluated in cell migration and cytotoxicity assays. The analogue designed by molecular simplification ((E)-N-acryloyl-3-(3,4,5-trimethoxyphenyl)acrylamide) was the most active of the series, with an EC50 of 1.5 ï¿½ 1 μM. Additionally, this compound was selectively cytotoxic, with a selectivity index (SI) of 4.4.
Keywords: Cell migration inhibition; Cytotoxicity; Piperamide; Piperlongumine; Piplartine